Aspek Perlindungan Hukum Terhadap Pencemaran Lingkungan - Mutriady, Anto (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
In accordance with Government Regulation Number 66 of 2014 concerning clean and healthy health, environmental health aims to create a healthy environmental quality, both from physical, chemical, biological and social aspects, which enables everyone to achieve the highest degree of clean health, especially the surrounding environment. its height. A clean and healthy environment is the dream of all levels of society, people have the right to an environment that is comfortable for themselves. Humans live in a world that determines their environment or is determined by their environment. The problem approach used is a normative and empirical legal approach. The type of data consists of secondary data and primary data, carried out using field studies and literature studies. Based on the results of environmental research in the Marelan area, the environmental conditions of the polluting community in the Marelan area have followed up on the pollution that occurred in the Marelan area. The form of pollution that occurs is rubbish and there are companies that pollute the environment in the Marelan area, including 10 factory companies that dump waste into the river, namely workshop waste, chips factory, tofu and tempeh food factory, shrimp manufacturing factory, retail syrup factory. Apart from that, there are inhibiting factors in legal protection of the community's environmental conditions due to pollution in the Marelan area, divided into (2) two factors, namely, internal and external factors. In order for legal protection of the community's environmental conditions due to pollution in the Marelan area to run well, the regional government must follow up well in accordance with Law Number 32 of 2009 concerning environmental protection and management.